THE EXPERIENCES OF THE REALIZATION OF PV POWER PLANTS AFTER IMPLEMENTATION OF THE PROSUMERS STATUS - Corba, Zoltan; Milićević, Dragan; Dumnic, Boris; Popadić, Bane (Journal on Processing and Energy in Agriculture, 2023)
The amendment of the Law on Energy and the adoption of the new Law on Renewable Energy Sources enabled a sudden increase in the installed capacity of photovoltaic (PV) power plants in the Republic of Serbia in 2022. Thanks to the new modality called prosumers, interest in the construction of PV power plants has increased, both with households and with commercials entities. The general situation in the world, crises, pandemics and wars have caused a drastic increase in the price of energy products, and therefore electricity. For contribute to the reduction of the negative impact of climate change, it is an ideal opportunity to use the production of electricity from one’s own power plant to compensate for increased costs for energy. The most affordable and simplest is the construction of the PV power plant, because solar energy reaches every roof. This paper describes the possibilities of building PV power plants in the status of prosumers from the technical and legal aspects. In addition to examples from practice, the current state of installed capacities of PV power plants in the Republic of Serbia in the status of prosumers is given.